2022
DOI: 10.3390/ijms23052619
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Training Regulation of Autophagy Markers in Human and Rat Skeletal Muscle

Abstract: Autophagy is a key intracellular mechanism by which cells degrade old or dysfunctional proteins and organelles. In skeletal muscle, evidence suggests that exercise increases autophagosome content and autophagy flux. However, the exercise-induced response seems to differ between rodents and humans, and little is known about how different exercise prescription parameters may affect these results. The present study utilised skeletal muscle samples obtained from four different experimental studies using rats and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Participants completed three work-matched experimental sessions at 51%, 59%, and 67% of peak aerobic power (Ẇ max ), representing –18%, –6% and+6% of the maximal lactate steady state (MLSS) – an important metabolic threshold delineating heavy from severe exercise intensity 59 . The findings from this study supported the intensity-independent nature of exercise-induced decreases in LC3B-II and LC3B-II/I ratio, and we observed no changes in p62 protein 47 ( Fig. 3-a ).…”
Section: Current Insights Into Exercise and Training-induced Regulati...supporting
confidence: 86%
See 4 more Smart Citations
“…Participants completed three work-matched experimental sessions at 51%, 59%, and 67% of peak aerobic power (Ẇ max ), representing –18%, –6% and+6% of the maximal lactate steady state (MLSS) – an important metabolic threshold delineating heavy from severe exercise intensity 59 . The findings from this study supported the intensity-independent nature of exercise-induced decreases in LC3B-II and LC3B-II/I ratio, and we observed no changes in p62 protein 47 ( Fig. 3-a ).…”
Section: Current Insights Into Exercise and Training-induced Regulati...supporting
confidence: 86%
“…In contrast to the rodent data, exercise in humans decreases markers of autophagosome content, which could be due to increased autophagic flux or decreased autophagosome biogenesis. Regarding autophagy receptors, most studies have shown unchanged p62 protein levels following endurance exercise [47,52,57,58]. Schwalm et al postulated that autophagy activation was dependent on exercise intensity [53].…”
Section: Endurance Exercisementioning
confidence: 99%
See 3 more Smart Citations